Ciclos políticos orçamentários no Estado do Ceará, 1986-2006 - Queiroz, Mário César Lemos (2009)
The political cycles’ perception is very intuitive, and, therefore, it is a well studied phenomenon. Among the theories developed there are four strands, arranged between the criteria of voter's rationality and politician's behavior, namely: the traditional opportunistic political cycle and the rational opportunistic one, as well as the traditional partisan political cycle and the rational partisan one. The political business cycles, however, may occur with combined features, like the political cycles ideologically motivated (partisan cycles) with some characteristics of opportunistic cycles. The political budget cycles, framed as the rational opportunistic type, are prioritized in this study, because it is believed, due to its simplicity of operation and the fact that democracy is a process still young, to be the ones most likely to occur in Brazil and, consequently, in Ceará. The proposed models’ intention was to evidence the opportunistic behavior of Ceará state's governors in the period from 1986 to 2006, externalized by cyclical movements of the budgetary execution. The data analysis, including graphic one, confirmed that the governors showed, in general, opportunistic behavior on the budgetary execution.